Karakteristik Pellet dari Bagas Tebu - Haryanto, Agus; Pratama, Yuko Armandho; Triyono, Sugeng; Suharyatun, Siti (Jurnal Agricultural Biosystem Engineering, 2023)
Sugarcane bagasse is the remaining solid waste from sugarcane (Sacharum officinarum) milling which has the potential to be developed as solid fuel in the form of pellets. The purpose of this study was to determine the effect of variations in pressure and particle size on the characteristics of pellets from sugarcane bagasse. The research was carried out with a combination of variations in particle size (fine, medium, and coarse) and pressure (1, 2, and 3 tons). The results showed that sugarcane bagasse has the potential to be developed as a pellet fuel because it has a relatively high calorific value, an average of 16.53 MJ/kg. Sugarcane bagasse pellets meet SNI 8675-2018 standards in terms of moisture content, density, and ash content. The results showed that although the ash content of the pellets was affected by the particle size, in general, the characteristics of the pellets were not significantly affected by the treatment factors (pressure and particle size as well as their interactions). Sugarcane bagasse pellets have a high water absorption capacity, so they require a good storage method. Keywords: Densification, Density, Pressure, Particl Size, Strength